2022
DOI: 10.1016/j.foreco.2021.119819
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on size distributions in spruce-fir-beech mixed stands across Europe

Abstract: Forest composed of Picea abies L., Abies alba Mill. and Fagus sylvatica L. cover a large area in the European mountain regions and have a high ecological and socio-economic importance as they supply many ecosystems services. Because of climate change, these forests are exposed to warming, and this effect increases with elevation, which may impact their delivery of goods and services. Previous studies did not find significant changes in the overall productivity of these species over the last 30 years, but they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Our findings confirmed previous findings depicting the effects of environmental factors on ingrowth (Klopcic et al, 2012;Li et al, 2011;Zell et al, 2019). For instance, increasing temperatures led to lower numbers of ingrowth trees due to temperature-induced stress, to a higher share of broadleaves, potentially even in alpine regions (Condés et al, 2022), and finally to higher dbh rates in maple, ash, and other broadleaves. Solar radiation emerges as a statistically significant positive driver of the number of ingrowth trees, likely because it leads to more light and energy resources.…”
Section: Ingrowth Modelssupporting
confidence: 91%
“…Our findings confirmed previous findings depicting the effects of environmental factors on ingrowth (Klopcic et al, 2012;Li et al, 2011;Zell et al, 2019). For instance, increasing temperatures led to lower numbers of ingrowth trees due to temperature-induced stress, to a higher share of broadleaves, potentially even in alpine regions (Condés et al, 2022), and finally to higher dbh rates in maple, ash, and other broadleaves. Solar radiation emerges as a statistically significant positive driver of the number of ingrowth trees, likely because it leads to more light and energy resources.…”
Section: Ingrowth Modelssupporting
confidence: 91%
“…As early as in the 19th century researchers reported that a mean annual temperature over 7.5 °C is not favorable for spruce (Schmidt-Vogt, 1977: 466). Beech is much more sensitive to low temperatures compared to spruce and negatively influenced by higher mean annual temperature (Condés et al, 2022). The positive effect of precipitation between two censuses (PCPPSP) on recruitment of beech and spruce indicates that a precipitation deficit not only affects the growth of adult trees (Mazza et al, 2014;Rohner et al, 2018;Felton et al, 2021), but also has a weak effect on recruitment.…”
Section: Effects Of Stand Site and Climate Characteristics On Tree Re...mentioning
confidence: 99%
“…Due to its high stability and predictability, research on the growth model of the stand basal area is a central focus in the modeling of stand measurement factors [4,5]. The stand basal area, intimately linked to species and stand productivity [6], is widely employed in estimating the dynamic changes in forest structure and resources and forms the foundation for formulating forest management plans [7].…”
Section: Introductionmentioning
confidence: 99%
“…The climate exerts a significant influence on forest growth [6,30]. It impacts crucial physiological and phenological processes in trees [31,32], leading to shifts in species distribution, forest composition, and productivity [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation